2019
DOI: 10.1186/s40738-019-0069-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genital Chlamydia trachomatis infection on reproductive outcomes among infertile women undergoing tubal flushing: a retrospective cohort at a fertility centre in Uganda

Abstract: Background: The impact of current C. trachomatis on clinical pregnancy and live birth rates among women undergoing tubal flushing is largely unknown. This study aimed to investigate whether current female genital C. trachomatis infection affects the chance of achieving a clinical pregnancy and a live birth, among infertile women undergoing tubal flushing, at a fertility centre in Uganda. Methods: A retrospective Cohort study at a peri-urban fertility centre. A total of 253 eligible women with tubal factor infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Davies et al, 12 Ramadhani et al, 14 and Kayiira et al, 19 by presenting results that strengthen the discussed association, claim that policies of routine screening and interventions focused on preventing both first and repeated infections are extremely important in order to improve women's long-term reproductive health. 12,14,19 The type of female infertility more commonly associated with CT infection is tubal factor infertility (TFI), which occurs due to tubal occlusion (Toye et al, 1993). 27 According to Hoenderboom et al, 22 CT positivity represents a fourfold higher risk for TFI.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Davies et al, 12 Ramadhani et al, 14 and Kayiira et al, 19 by presenting results that strengthen the discussed association, claim that policies of routine screening and interventions focused on preventing both first and repeated infections are extremely important in order to improve women's long-term reproductive health. 12,14,19 The type of female infertility more commonly associated with CT infection is tubal factor infertility (TFI), which occurs due to tubal occlusion (Toye et al, 1993). 27 According to Hoenderboom et al, 22 CT positivity represents a fourfold higher risk for TFI.…”
Section: Discussionmentioning
confidence: 93%
“…This is also expressed in den Heijer et al 23 finding that CT-positive women had approximately 70% higher chance of experiencing infertility. Davies et al, 12 Ramadhani et al, 14 and Kayiira et al, 19 by presenting results that strengthen the discussed association, claim that policies of routine screening and interventions focused on preventing both first and repeated infections are extremely important in order to improve women's long-term reproductive health. 12 14 19 …”
Section: Discussionmentioning
confidence: 93%
“…This finding is comparable to those reported by others and suggests that a history of vaginal infection may be the major risk factor for chlamydial infection. Kayiira et al showed that over 36.96% of the participants with current genital C. trachomatis had a history of genital infection compared to 2.9% of participants in the non-exposed group (21). Nevertheless, the fact that the sample size did not achieve statistical power can explain the lack of association between C.…”
Section: Discussionmentioning
confidence: 99%
“…den Heijer et al also found that CT-positive women were 70% more likely to experience infertility [112]. Davies [113], Ramadhani [114], and Kayiira [115] also showed results that reinforce this relationship in different countries and populations, noting that routine chlamydia screening, along with interventions to prevent initial and recurrent infections, is extremely important to protect women's long-term reproductive health.…”
Section: Infertility: a Major Complication Of C Trachomatis Infectionmentioning
confidence: 98%